Análise dos registros de nascimentos vivos em localidade urbana no Sul do Brasil Analysis of legal registration of live births in an urban area of Southern Brazil - Maria Helena P. de Mello Jorge; Sabina Léa Davidson Gotlieb; Selma Maffei de Andrade (Universidade de São Paulo, 1997)
Foram analisados os nascimentos vivos de mulheres residentes em Londrina, Paraná, (Brasil), ocorridos entre abril e setembro de 1994 (4259), a partir das duas vias das Declarações de Nascidos Vivos (DN) - vias brancas (provindas dos hospitais onde ocorreram os nascimentos) e amarelas (vindas dos Cartórios onde houve o registro) - recebidas pelo Serviço Municipal de Saúde. Visitas domiciliárias foram realizadas nos casos em que não houve o pareamento das respectivas vias da DN de cada criança (possível caso de sub-registro ou parto domiciliar). A taxa de sub-registro de nascimento vivo foi estimada entre 5,3% e 6,6%; o custo foi o principal motivo alegado para o não registro, seguido da negligência e legitimidade. Dos que foram registrados, em 88,7% o mesmo ocorreu até 60 dias após o parto e o tempo médio para o registro foi de 26,5 dias (com desvio-padrão de 52 dias).Variáveis estatisticamente associadas aos fatos de registrar e ter sido no tempo legal (60 dias) foram tipo de parto, instrução e idade materna. Estimativa da proporção de partos domiciliares entre os nascimentos registrados foi um valor entre 0,1 e 0,3%, sendo as razões alegadas: "opção por parte da mãe", "falta de condução para ser removida para o hospital" e "não deu tempo de chegar no hospital". Live births which occurred in the period from April to September of 1994 were analysed, using the two copies of the Birth Declaration-BD-( the white copy coming from the hospital where the child was born and the yellow copy sent by the Legal Registry Office where the birth was registered) received by the Londrina Municipal Health Service. After the "cross matching"of both copies (for each child), household interviews were performed in cases without matched pairs (only a white or only a yellow copy indicating possibly unregistered or home deliveries). Results showed that the proportion of births not legally registered was of from 5.3 to 6.6% of the hospital births. Cost, negligence and legitimacy were the main reasons given for not registering births legally. The average time taken to make the registration was 26.5 days( standard deviation of 52 days) and 88.7% of the families did it by the 60th day from the date of the birth. A statistical association was detected between the act of registration and the period within which registration is required (within 60 days from birth) and type of delivery, maternal age and education. The official proportion of home deliveries was 0.5%;however, after the research the value was found to be somewere between 0.13 and 0.3% of all the registered births - only 36.8% were really born at home. Reasons for home deliveries were: option, "there wasn't a means of transport to take the pregnant woman to hospital" and "there wasn't enough time to get to a hospital".